Chronology of the western world, 1500-1900 AD - Society for Visual Education (Chicago, IL The Society, 1988)
Examines the western world and the achievements of its artists, scientists, philosophers, and politicians. Looks at the exploration of the New World.
VHS.
Keywords: History, Modern; History, Modern; World history -- 1500-1900 A.D. .